2018
DOI: 10.1111/ecc.12930
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practice of surgeons regarding nutritional support in CRS and HIPEC patients: Are we missing something?

Abstract: Nutrition’s impact on the surgical outcome has been established in various surgical specialties. However, data addressing the nutritional aspect following surgery for peritoneal surface malignancies are considered scarce. We aim to evaluate the knowledge, attitudes, and practice of surgeons regarding their nutritional support for patients undergoing cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS and HIPEC) via a survey directed to self‐evaluate nutritional knowledge, screening, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In contrast, ESPEN guidelines recommend nutritional status assessment before and after major surgery, and in every patient undergoing cancer-related surgery, the most frequent reason for GI surgery in this survey [6,24]. Underutilization of nutritional screening has been reported in other surgeon surveys [25,26]. For example, many general surgeons in Turkey only conducted nutritional screening in patients who looked malnourished (41.1%), with just 24.6% screening all individuals [27].…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, ESPEN guidelines recommend nutritional status assessment before and after major surgery, and in every patient undergoing cancer-related surgery, the most frequent reason for GI surgery in this survey [6,24]. Underutilization of nutritional screening has been reported in other surgeon surveys [25,26]. For example, many general surgeons in Turkey only conducted nutritional screening in patients who looked malnourished (41.1%), with just 24.6% screening all individuals [27].…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, nutritional screening is strongly encouraged in hospitals and residential settings [ 19 ]. However, the attention given to managing nutritional problems in the elderly is considered poor [ 5 ], and data on undernutrition in intermediate care are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, screening for undernutrition is considered poor in older adults [ 5 ]. Previous studies have shown a lack of attentive healthcare around clinical nutrition by professionals [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The positive trend reported for surgeons dedicated to PSM, is consistent with a previous study conducted among the attendees of the International Regional Cancer Therapies Symposium in 2017. Although only 35.19% reported the availability of screening tools, 86.5% of participants stated that their CRS/HIPEC patients have access to a dietician referral [15]. This is of striking importance, since the vast majority of patients undergoing HIPEC and CRC are treated with multiple abdominal organ resections and chemotherapy drugs; malnutrition in these patients is reported with a prevalence of 33% and correlated with hospitalization and postoperative infections [8].…”
Section: Discussionmentioning
confidence: 99%